Usefulness of the acoustic speech signal information in the nervous system evaluation - BASZTURA, Cz.; PODEMSKI, R. (Archives of Acoustics, 1996)
In the paper a preliminary analysis of the possibilities of using a speech signal for the objective diagnostics assistance, as well as for monitoring the process of the reconvalescence from the nervous system diseases, was presented. This paper presents also a conception of the acoustic speech signal computer analysis for some nervous pathological states. The possibilities of making acoustic patterns for the dysarthria disease states from distinctive acoustic parameters compared to the physiological standards, are also described in the papers. The paper presents conditions required for making speech pathology that can determine the kind, and in some cases, even the localization of the nervous system changes. The examples of the acoustic pictures of different types of dysartrhia compared to the psychological standards, were also described in the papers. The examples of the acoustic patterns of different types of dysartrhia compared to the psychological standards were described, and future research directions are set.